Shape Grammar for House Facade along the Alley in Urban Kampung, Tambora, Jakarta - Irma Desiyana (RUAS, 2022)
The shape grammar can reveal the socio-spatial uniqueness that moulds the geometric shapes and elements of the house facade in a dense area of the urban kampung. The façade tends to not have the exact pattern due to adjustment of daily activities and needs in Tambora Jakarta. However, the grassroots have formed the pattern of events along the alley that represents contexts like milieu, economics, and social conditions. The alley has overlapping layers between private and public activities, which contribute to the geometric shapes and elements of the façade in Tambora. The house facade depicts activities and relationships inside and outside that manifest in geometric shapes and elements of the facade. Hereafter, this research combines the shape grammar for the geometric pattern of the facade and the pattern language for the qualitative contexts. The first step is categorising the geometric shapes and elements of the facade and the socio-spatial aspects into defined shape rules. Then, mapping the pattern language of activities and needs between inside–house program and outside–the use of space along the alley to delineate spatial relation. The result intends to comprehend the correlation between the logic of the geometric shape and facade elements concerning the qualitative context.